GMP-Compliant Manufacturing of NKG2D CAR Memory T Cells Using CliniMACS Prodigy - Fernández, Lucía; Fernández, Adrián; Mirones, Isabel; Escudero, Adela; Cardoso, Leila; Vela, María; Lanzarot, Diego; de Paz, Raquel; Leivas, Alejandra; Gallardo, Miguel; Marcos, Antonio; Romero, Ana Belén; et al. (Frontiers in Immunology, 2019)
NKG2D is a NK cell activating receptor that recognizes different stress-induced ligands that are overexpressed in a variety of childhood and adult tumors. NKG2D CAR T cells have shown potent anticancer effects against different cancer types. A second-generation NKG2D CAR was generated by fusing full-length human NKG2D to 41BB costimulatory molecule and CD3ζ signaling domain. Patient-derived CAR T cells show limitations including inability to manufacture CAR-T cells from the patient’s own T cells, disease progression and death prior to return of engineered cells. The use of allogeneic T cells for CAR therapy could be an attractive alternative, although undesirable graft versus host reactions may occur. To avoid such adverse effects, we used CD45RA- memory T cells, a T cell subset with less alloreactivity, as effector cells to express NKG2D CAR. In this study we developed a protocol to obtain large-scale NKG2D CAR memory T cells for clinical use by using CliniMACs Prodigy, an automated closed system compliant with GMP guidelines. CD45RA+ fraction was depleted from healthy donor´s non-mobilized apheresis using CliniMACS CD45RA Reagent and CliniMACS Plus device. A total of 108 CD45RA- cells were cultured in TexMACS media supplemented with 100 IU/ml IL-2 and activated at day 0 with T Cell TransAct. Then, we used NKG2D-CD8TM-41BB-CD3ζ lentiviral vector for cell transduction (MOI = 2). NKG2D CAR T cells expanded between 10-13 days. Final cell products were analyzed to comply with the specifications derived from the quality and complementary controls carried out in accordance with the instructions of the Spanish Regulatory Agency of Medicines and Medical Devices (AEMPS) for the manufacture of Investigational Advanced Therapy Medicinal Products (ATMPs). We performed four validations. The manufacturing protocol here described achieved large numbers of viable NKG2D CAR memory T cells with elevated levels of NKG2D CAR expression and highly cytotoxic against Jurkat and 531MII tumor target cells. CAR T cell final products met release criteria, except for one showing myc overexpression and another with viral copy number higher than 5. Manufacturing of clinical-grade NKG2D CAR memory T cells using CliniMACS Prodigy is feasible and reproducible, widening clinical application of CAR-T cell therapies.